DNA variants in CACNA1C modify Parkinson disease risk only when vitamin D level is deficient. (June 2016) - Wang, Liyong; Maldonado, Lizmarie; Beecham, Gary W.; Martin, Eden R.; Evatt, Marian L.; Ritchie, James C.; Haines, Jonathan L.; Zabetian, Cyrus P.; Payami, Haydeh; Pericak-Vance, Margaret A.; Vance, Jeffery M.; Scott, William K.
Abstract : Objective: To evaluate the association between the genetic variants in CACNA1C, which encodes the α1 subunit of the L-type voltage-sensitive calcium channel (LVSCC) and Parkinson disease (PD) while accounting for interactions with vitamin D concentration. Methods: Two independent case-control data sets (478 cases and 431 controls; 482 cases and 412 controls) were used. Joint effects of single nucleotide polymorphisms (SNPs) and SNP-vitamin D interaction were analyzed by comparing models containing vitamin D deficiency, SNP genotypes, SNP-vitamin D interaction, and covariates to a restricted model with only vitamin D deficiency and covariates. Meta-analysis was used to combine the joint effects in the 2 data sets. Analysis was stratified by vitamin D deficiency to demonstrate the pattern of SNP-vitamin D interaction. Results: Vitamin D deficiency was associated with PD in both data sets (odds ratio [OR] = 1.9–2.7, p ⩽ 0.009). SNP rs34621387 demonstrated a significant joint effect (meta-analysis, p = 7.5 × 10 −5 ; Bonferroni corrected, p = 0.02). The G allele at rs34621387 is associated with PD in vitamin D-deficient individuals in both data sets (OR = 2.0–2.1, confidence interval = 1.3–3.5, p = 0.002) but is not associated with PD in vitamin D–nondeficient individuals ( p > 0.8 in both data sets). Conclusions: Previous studies suggest that vitamin D deficiency is associated with PD and sustained opening of LVSCC contributes to the selective vulnerability of dopaminergic neurons in PD. Our data demonstrate that the association between genetic variations in CACNA1C and PD depends on vitamin D deficiency, providing one potential mechanism underlying the association between vitamin D deficiency and PD.